Influencing across multiple levels: The positive effect of a school-based intervention on food waste and household behaviours. (15th April 2022) - Boulet, Mark; Grant, Wendy; Hoek, Annet; Raven, Rob
Abstract: Changing consumer food waste-related behaviours is critical to meeting global targets of halving food loss and waste. This paper presents a food waste reduction intervention trialled in five Australian schools and explores its influence on food provisioning practices, changed behaviours and food waste. Consisting of a mix of educational, skills-based, and whole-of-school-events, the intervention sought to reduce food waste by encouraging students to be more involved at home in choosing and/or preparing food to take to school. Students reported greater involvement in the target behaviours and there was a reduction in avoidable food waste in participating schools. Utilising a multi-level perspective, this study demonstrates how food-related practices and behaviours emerge from the interactions of macro and meso-level factors and highlights the value of this perspective when designing food waste reduction interventions. Highlights: The effects of a school-based intervention on food waste and household food-related behaviours were tested. The intervention had a statistically significant effect on targeted behaviours of parents and students at home. There were observable reductions in avoidable food waste at participating schools. Interventions in external settings such as schools can reduce food waste and influence food provisioning within homes. We call for multi-level interventions to influence consumer behaviours and reduce food waste.